Infographic. High rate of second ACL injury following ACL reconstruction in male professional footballers: an updated longitudinal analysis from 118 players in the UEFA Elite Club Injury Study - Della Villa, F.; Hägglund, M.; Della Villa, S.; Ekstrand, J.; Waldén, M. (British Journal of Sports Medicine, 2021)
ACL injury is a serious concern for the professional football player.1 Studies about second ACL injury rate and career length after ACL reconstruction (ACLR) in male professional football players are scarce in the current literature.